Electronic Judicial Declaration and its Impact Simplification of Litigation Procedures in the Sultanate of Oman, Analytical Study - AL Kharusi, Dawood Sulaiman (Journal of Ecohumanism, 2025)
Electronic judicial declaration is a form of access to judicial protection through the use of electronic means of assistance to the human race, through technical procedures that ensure the realization of the principles and guarantees of litigation under the legislative protection of those procedures in accordance with the general rules and principles of the Code of Civil and Commercial Procedure, taking into account the special nature of electronic means The electronic judicial declaration is characterized by the easy use and preservation of documents and documents, with the result that there is little loss of case files or change in the location of their preservation and the high level of security of trial records due to the fact that electronic documents and documents are more credible and easier to detect or modify any change in them, as well as easy access to them. The Omani legislature has identified several electronic means of making an electronic judicial declaration: telephones, fax numbers and electronic addresses; Agent’s telephone number, email address and fax number. The adoption of the judicial declaration through modern technological media is an important step in reducing the length of litigation in the courts of the Sultanate of Oman